The Impact of General Self-Efficacy on Psychological Resilience During the COVID-19 Pandemic: The Mediating Role of Posttraumatic Growth and the Moderating Role of Deliberate Rumination - Zeng, Wei; Wu, Xingrou; Xu, Yanhua; Wu, Jiamin; Zeng, Yuqing; Shao, Jinlian; Huang, Dongtao; Zhu, Ziqi (Frontiers in Psychology, 2021)
Purpose: This study used a moderated mediation model to explore the relationship between general self-efficacy (GSE) and psychological resilience (PR) and the associated mechanisms, the mediating role of posttraumatic growth (PTG), and the moderating role of deliberate rumination (DR) during the coronavirus disease 2019 (COVID-19) pandemic. Knowledge of the relationship between these four variables examined further understanding of the PR improvement mechanism of college students and even the general public. Methods: The college students who participated in this study came from an independent college in Guangdong Province, China. A total of 918 college students completed the survey, and the final data sample size was 881. SPSS 23.0 and PROCESS (version 3.3) were used to conduct Pearson's correlation analysis and hierarchical regression linear analysis on the data. Results: (1) The correlation analysis showed that GSE and PR were positively correlated and that PTG was positively correlated with GSE and PR. DR was positively correlated with GSE, PTG, and PR. (2) The results of mediation analysis showed that GSE had a direct predictive effect on DR, and PTG partially mediated the relationship between the two. (3) The results of moderating effect analysis showed that DR hindered the effect of GSE on PTG but enhanced the positive impact of PTG on PR. Conclusions: General self-efficacy can improve PR under the mediating influence of PTG. DR played a positive moderating role in the relationship between GSE and PTG, and played a negative moderating role in the relationship between PTG and PR. These results advance the understanding of the mechanism between GSE and PR.